THE ANALYSIS OF STUDENTS' ACTIVITY IN SOCIAL NETWORK - Vasiliy V. Krasil'shchikov; Mitrofan A. Osetrov (Высшее образование в России)
This paper gives the analysis of social interaction of students. Methods of mathematical modeling of networks, Graph Theory, and Statistics were used. The research of the personal pages in the social network «VKontakte » of full-time courses students of Vladimir branch of the Russian University of Cooperation was conducted to illustrate the methods. The proposed approach enables to reveal students with the developed social and cognitive competences, high level of consciousness and advanced in the intellectual development. The special organization of the activity of such students will increase the efficiency of training process at University.